2010
DOI: 10.1128/jvi.00701-10
|View full text |Cite
|
Sign up to set email alerts
|

Glycine 184 in Nonstructural Protein NS1 Determines the Virulence of Influenza A Virus Strain PR8 without Affecting the Host Interferon Response

Abstract: The nonstructural protein NS1 of influenza A virus counteracts the interferon (IFN) system and thereby promotes viral replication. NS1 has acquired different mechanisms to limit induction of IFN. It prevents double-stranded RNA (dsRNA) and RIG-I-mediated activation of interferon regulatory factor 3 (IRF3), and it blocks posttranscriptional processing of cellular mRNAs by binding to the cleavage and polyadenylation specificity factor (CPSF). Using a mouse-adapted A/PR/8/34 virus and reverse genetics to introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
90
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(100 citation statements)
references
References 63 publications
9
90
1
Order By: Relevance
“…The nonstructural (NS1) protein of influenza A viruses is well recognized as a virulence element and for its function in antagonizing the host immune response (11,15,18,25). It has been suggested that there may be multiple levels of interaction between NS1 and components of the host antiviral response (25,44). It was also recently reported that NS1 interacts with NP, although the details of the biological significance of this interaction remain un- At 4 h postinfection, the NS1 and RAP55 proteins were detected by costaining with rabbit anti-NS1 polyclonal antibodies (red) and mouse anti-RAP55 monoclonal antibodies (green).…”
Section: Discussionmentioning
confidence: 99%
“…The nonstructural (NS1) protein of influenza A viruses is well recognized as a virulence element and for its function in antagonizing the host immune response (11,15,18,25). It has been suggested that there may be multiple levels of interaction between NS1 and components of the host antiviral response (25,44). It was also recently reported that NS1 interacts with NP, although the details of the biological significance of this interaction remain un- At 4 h postinfection, the NS1 and RAP55 proteins were detected by costaining with rabbit anti-NS1 polyclonal antibodies (red) and mouse anti-RAP55 monoclonal antibodies (green).…”
Section: Discussionmentioning
confidence: 99%
“…At 9 h after influenza virus infection, the total RNA of infected cells was isolated using TRIzol reagent (Invitro-gen, USA). To determine the relative amounts of IFN-␤ pre-mRNA and mRNA, the total RNA was subjected to a reverse transcription reaction with an oligonucleotide complementary to sequence downstream of the poly(A) addition site of IFN-␤ pre-mRNA and an oligo(dT) primer using SuperScript III reverse transcriptase (Life Technologies, USA) (15,20), and quantitative PCR (qPCR) was conducted subsequently to detect the pre-mRNA of IFN-␤ and the mRNAs of IFN-␤ and ␤-actin using Kapa SYBR fast qPCR kits (Kapa Biosystems, USA) with primers described previously (15,20) and a Roche LightCycler 480II instrument.…”
Section: Methodsmentioning
confidence: 99%
“…The effector domains of NS1 proteins encoded by H3N2, H2N2, and seasonal H1N1 viruses strongly bind to the 30-kDa subunit of the cleavage and polyadenylation specificity factor (CPSF30), thereby inhibiting the 3= end processing of host pre-mRNAs and the production of mature mRNAs, including beta interferon (IFN-␤) and other antiviral mRNAs (11)(12)(13). However, the NS1 proteins encoded by some strains of influenza A viruses, such as Puerto Rico/8/34/H1N1 (PR8) and the 2009 pandemic H1N1 viruses, do not efficiently bind CPSF30 (13)(14)(15). Consequently, these viruses depend solely on the ability of their NS1 proteins to efficiently suppress the activation of interferon regulatory factor 3 (IRF3) to inhibit the expression of type I IFN.…”
mentioning
confidence: 99%
“…The minigenome expression plasmids were cotransfected into HEK293 cells together with influenza virus NP, PB1, PB2, and PA protein expression plasmids and with a transfection control renilla luciferase expression plasmid. Reporter gene activity was measured using a dual luciferase reporter assay (Promega, Madison, WI), as previously described (29). As a negative control, transfections were performed in the absence of the plasmid coding for NP.…”
mentioning
confidence: 99%